2015
DOI: 10.1038/cddis.2014.590
|View full text |Cite
|
Sign up to set email alerts
|

Lack of gp130 expression in hepatocytes attenuates tumor progression in the DEN model

Abstract: Chronic liver inflammation is a crucial event in the development and growth of hepatocellular carcinoma (HCC). Compelling evidence has shown that interleukin-6 (IL-6)/gp130-dependent signaling has a fundamental role in liver carcinogenesis. Thus, in the present study we aimed to investigate the role of gp130 in hepatocytes for the initiation and progression of HCC. Hepatocyte-specific gp130 knockout mice (gp130Δhepa) and control animals (gp130f/f) were treated with diethylnitrosamine (DEN). The role of gp130 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
27
0
4
Order By: Relevance
“…In the autochthonous tumour models, the severity of the phenotype also correlates with the extent of liver inflammation, being stronger in Δhep than in Δp/np animals. This is consistent with the fact that increased YAP1 expression promotes hepatocyte proliferation in vivo only upon liver injury or inflammation, that IL6 cooperates with YAP1 in this setting35, and that GP130 is necessary for full-fledged DEN-induced tumourigenesis in the mouse14.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the autochthonous tumour models, the severity of the phenotype also correlates with the extent of liver inflammation, being stronger in Δhep than in Δp/np animals. This is consistent with the fact that increased YAP1 expression promotes hepatocyte proliferation in vivo only upon liver injury or inflammation, that IL6 cooperates with YAP1 in this setting35, and that GP130 is necessary for full-fledged DEN-induced tumourigenesis in the mouse14.…”
Section: Discussionsupporting
confidence: 86%
“…Increased GP130 expression selectively supports the activation of STAT3 by proinflammatory cytokines of the IL6 family, but not by those of the IL10 family, broadly speaking anti-inflammatory in nature; the importance of the GP130/STAT3 axis in epithelial inflammation and gastrointestinal tumourigenesis22 and of GP130 in liver tumours47144041 has been amply documented. Besides the cell-autonomous proliferation phenotype, RAF1-deficient DIH are much more efficient than controls in attracting macrophages; they also produce higher amounts of CCL2, a STAT3 target gene42, and of CXCL1, upregulated by YAP1 in breast cancer cell lines43.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic activation of proinflammatory pathways is critical to the progression of hepatitis to liver cancer. Among numerous proinflammatory factors, interleukin‐6 (IL6)‐mediated signaling has been extensively studied in the context of chronic liver diseases and HCC development . One study found elevated IL6 levels in 40% of liver cancer patients, which suggests that IL6 is associated with HCC progression .…”
mentioning
confidence: 99%
“…Among numerous proinflammatory factors, interleukin‐6 (IL‐6) is the most prominently elevated in almost 40% of liver cancer patients, suggesting that IL‐6 is associated with HCC progression 81, 82, 83, 84, 85, 86, 87. The TGF‐β pathway induced IL‐6 secretion may confer chemotherapeutic resistance in HCC 32.…”
Section: Tgf‐β In An Invasive Cancer Stem Cell Modelmentioning
confidence: 99%